Towards a maturity model for higher education institutions - Duarte, Nuno (2011)
The adoption of business process improvement strategies is currently a concern of most organizations. The quest for the benefits of this improvement on resource optimization and the responsiveness of the organizations has raised several proposals for process improvement methodologies. These approaches differ both in the principles that support them, and in the specific area to which they are intended. However, proposals and results of scientific research on process improvement in higher education institutions, extremely complex and unique organizations, are still scarce. This research project aims to propose an extension to a business process maturity model for this particular type of organizations.